Pelatihan Pembuatan Bibit Stek Batang Kiara Karasak (Ficus Kurzii King) untuk Rehabilitasi di Desa Cimara Kecamatan Cibeureum, Kuningan - Hendrayana, Yayan; Adhya, Ilham; Supartono, Toto; Herlina, Nina; Siti Tamala; Unan Nur Abain; Alwi Zulva Maulida; Danda Priyana (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Cimara Village, Cibeureum District, Kuningan Regency, faces the problem of critical land which is at risk of environmental degradation due to erosion and reduced natural vegetation. This condition threatens soil fertility and reduces ecosystem function in maintaining environmental balance. One step that can be taken to restore this condition is land rehabilitation using local plants such as kiara karasak (Ficus kurzii King), which has high adaptability to the local environment and plays an important role in preventing soil erosion. The aim of this service is to provide training to the community regarding techniques for making Kiara Karasak stem cuttings, which is expected to support sustainable land rehabilitation programs. Methods for carrying out activities include introducing kiara karasak plants, training in selecting healthy stems suitable for cuttings, correct cutting techniques, use of root-stimulating hormones, as well as sowing and caring for seedlings so that they grow optimally. The approach used is participatory with direct practice in the field, so that participants can apply each stage independently. In this training, participants are also trained in caring for seedlings until they are ready to be moved to rehabilitation land. The results of the service showed that participants experienced a significant increase in their understanding and technical skills in making cuttings. They feel better prepared to produce Kiara Karasak seeds independently and contribute to land rehabilitation in Cimara Village. This activity is expected to have a long-term positive impact on improving environmental quality and increasing public awareness in maintaining the sustainability of the local ecosystem